Impact of the geometry of inclusions at the micro-scale on the overall stochastic properties. Issue 2 (1st February 2016) - Miranda, H. D.; Andrade Pires, F. M.; Marques, A. T.
ABSTRACT: In this contribution, the establishment of relationships between the microstructure of the material and the macroscopic properties is numerically investigated. The material under study is composed by inclusions randomly distributed on a uniform matrix and its heterogeneous nature is characterized by the size, shape, spatial distribution, and properties of the inclusions. To conduct these analyses, a general framework that generates and simulates representative volume elements (RVEs) based on the commercial finite element (FEM) software ABAQUS and existing homogenization techniques is developed. Two- and three-dimensional RVEs are generated and the variation of the properties investigated using a statistical approach.